Uterine artery pulsatility index reference chart selection between 24 and 40 weeks of gestational age for a health institution in Lima, Peru - Diez Chang, Guillermo (2020)
Uterine artery resistance is assessed to detect inadequate placentation in pregnant women, that increases the risk to develop preeclampsia, intrauterine growth restriction and other complications associated with placental insufficiency. Objective: To identify the uterine arteries pulsatility index (UtAPI) reference chart that best fits our institutional data. Methods: Retrospective, cross-sectional study that evaluated 1 753 single pregnancies; 2 031 UtAPI measurements of the uterine arteries were obtained. Mean UtAPI was compared with the reference charts published by Gomez, Limay and Weichert. Results: There was a mild but significant (r=0.16) negative correlation between UtAPI and gestational age between 24 and 40 weeks of gestation; 6.5%, 7.5% and 15% of our measurements were above the 95 centile of respectively Weichert, Limay and Gomez reference charts. Conclusions: In our population, the UtAPI distribution fitted best with Weichert reference chart. More prospective studies are needed to validate this clinical finding.